Faecalibacterium prausnitzii prevents hepatic damage in a mouse model of NASH induced by a high-fructose high-fat diet - Shin, Ji-Hee; Lee, Yoonmi; Song, Eun-Ji; Lee, Dokyung; Jang, Seo-Yul; Byeon, Hye Rim; Hong, Moon-Gi; Lee, Sang-Nam; Kim, Hyun-Jin; Seo, Jae-Gu; Jun, Dae Won; Nam, Young-Do (Frontiers in Microbiology, 2023)
Introduction Nonalcoholic steatohepatitis (NASH) is an advanced nonalcoholic fatty liver disease characterized by chronic inflammation and fibrosis. A dysbiosis of the gut microbiota has been associated with the pathophysiology of NASH, and probiotics have proven helpful in its treatment and prevention. Although both traditional and next-generation probiotics have the potential to alleviate various diseases, studies that observe the therapeutic effect of next-generation probiotics on NASH are lacking. Therefore, we investigated whether a next-generation probiotic candidate, Faecalibacterium prausnitzii, contributed to the mitigation of NASH. Methods In this study, we conducted 16S rRNA sequencing analyses in patients with NASH and healthy controls. To test F. prausnitzii could alleviate NASH symptoms, we isolated four F. prausnitzii strains (EB-FPDK3, EB-FPDK9, EB-FPDK11, and EB-FPYYK1) from fecal samples collected from four healthy individuals. Mice were maintained on a high-fructose high-fat diet for 16 weeks to induce a NASH model and received oral administration of the bacterial strains. Changes in characteristic NASH phenotypes were assessed via oral glucose tolerance tests, biochemical assays, and histological analyses. Results 16S rRNA sequencing analyses confirmed that the relative abundance of F. prausnitzii reduced significantly in patients with NASH compared to healthy controls (p < 0.05). In the NASH mice, F. prausnitzii supplementation improved glucose homeostasis, prevented hepatic lipid accumulation, curbed liver damage and fibrosis, restored damaged gut barrier functions, and alleviated hepatic steatosis and liver inflammation. Furthermore, real-time PCR assays documented that the four F. prausnitzii strains regulated the expression of genes related to hepatic steatosis in these mice. Discussion Our study, therefore, confirms that the administration of F. prausnitzii bacteria can alleviate NASH symptoms. We propose that F. prausnitzii has the potential to contribute to the next-generation probiotic treatment of NASH.